La loi, la statue et l’artiste. L’apport du droit moral aux débats sur la commémoration - Le Moine, François (RACAR : Revue d'art canadienne / Canadian Art Review, 2021)
Contemporary public sentiment and policy relating to the continued display of contested monuments has had a tendency to overlook (if not ignore) the rights of artists. This article reviews how the law, in particular, moral rights contained in the Copyright Act, protects artists and prevents statues and other public works of art from being “distorted, mutilated or otherwise modified.” For example, this provision—Paragraph 28.2(1)(a) of the Copyright Act—prevents certain types of changes from being made, including the repositioning or recontextualization of controversial monuments. Drawing from relevant case law and case studies of events that have been hotly debated in the media, we provide a summary of the applicable rules with the goal of integrating them into the ongoing discussion about commemoration. It is our hope that future decisions and public policies regarding contested monuments will be more conscious of the applicable legal framework and furthermore provide artists and their works the respect they deserve.